RELATIONSHIP OF MASTICATION CAPABILITY AND NUTRITION STATUS OF ELDERLY BUGINESE AND MANDARNESE: HUBUNGAN KEMAMPUAN PENGUNYAHAN DENGAN STATUS GIZI LANJUT USIA PADA SUKU BUGIS DAN MANDAR - Bahruddin Thalib (Dentika: Dental Journal, 2010)
The effect of mastication disorder in elderly caused difficulty in chewing hard or tough food leads to change eating patternto softer food. As a result, the tendency to eat softer, prepared, fast food, sugar, carbohydrate and soda is increased. Thisstudy aimed to find out the relationship of mastication capability to nutrition status in elderly Buginese and Mandarnese,and the difference of diets between both cultures as adaptability to food pattern and eating habit. Four hundred subjectstaken using purposive sampling, sample aged 55 years old and above, nutrition status was taken directly (anthropometric)BB/TB2 and mastication capability taken with custom questioner along with scoring value. The result showed that elderlyBuginese had 64.9% with poor nutrition status caused by poor mastication capability, mastication capability and nutritionstatus in elderly Buginese had significant relation (p=0.04), while elderly Mandarnese had 39.8% with poor nutritionstatus caused by poor mastication capability, but statistically, the relation between mastication capability with nutritionstatus in elderly Mandarnese was not significant (p=0.076). As conclusion there was significant relationship betweenmastication capability and nutrition status in Buginese and Mandarnese, and mastication capability and nutrition status ofMandarnese were better than Buginese.